Implantable cathodic voltage controlled electrical stimulator. Issue 23 (1st November 2019) - Weeks, K.; Clark, C.; Tobias, M.; McDermott, E.; Duquin, T.; Ehrensberger, M.; Titus, A.H.
Abstract : This work reports the first of its kind custom implantable cathodic voltage controlled electrical stimulator (iCVCES) for use with implanted orthopaedic devices. The iCVCES allows researchers to study DC cathodic voltage controlled electrical stimulation (CVCES) in vivo with no percutaneous leads. The iCVCES is a microcontroller‐based potentiostat circuit with wireless (bluetooth) communication that controls the DC cathodic stimulation and monitors the environment around the implant. Comprising a single PCB with a coin cell battery, the device is able to hold a constant voltage as large as −1.8 V in a dynamic impedance environment. In vitro tests demonstrate functionality comparable to bench‐top systems, and in vivo tests demonstrate operation in live rats, for up to 8 days, with the ability to provide constant stimulation with a maximum variation of 2 mV.